Understanding the Poverty Trap in Indonesia: Challenges for Inclusive Economic Development - Susi Sugiyarsih (International Journal of Science Education and Cultural Studies, 2023)
Despite several development programs and economic policies implemented over the years, poverty remains a major challenge in Indonesia. Many low-income households are confronted with conditions that are difficult to escape due to limited access to education, employment opportunities and productive resources. This is sometimes referred to as a poverty trap, where economic deprivation is passed down the generations and becomes a barrier to wider social and economic progress. This paper discusses the poverty trap within the framework of inclusive economic development. This study uses a narrative literature review approach to explore several academic works, policy reports and relevant publications related to poverty, unemployment, human capital and economic development in Indonesia. The focus is placed on understanding the interrelations of different socio-economic factors and their contribution to the perpetuation of poverty.  The review argues that poverty cannot be explained by low income alone. Educational disparities, limited employment opportunities, low productivity and unequal access to economic resources are all closely intertwined and frequently mutually reinforcing. This means that even with a growing economy, many people are finding it hard to improve their living conditions. These findings suggest that poverty reduction is not a matter of short-term assistance programs but needs to be accompanied by longer-term investments in education, skills development, job creation and economic inclusion.  An important challenge for Indonesia still to be addressed is poverty trap. The development of human capital and the expansion of economic opportunities are central to the promotion of inclusive development and the improvement of the welfare of vulnerable populations.